Regulators of ovarian functions - Sirotkin, Alexander V. (Obstetrics and gynecology advances., 2010)
This book represents an attempt to review the most recent knowledge concerning basic processes occurring in the most important female reproductive organ - the ovaries and their regulators. The most important processes (ovarian cyclic changes and oogenesis), as well as their extracellular (hormones and growth factors) and intracellular (protein kinases, transcription factors, small RNAs) regulators are described. Data concerning processes or substances well described in previous reviews are summarized here in a short form with references to corresponding reviews.